Systematic Comparison of Civics Learning Models in Elementary Schools: Indonesia Versus Finland - Hidayat, Muhamad Taufik; Hazima, Atika Azzahro (Journal of Teaching and Learning, 2026)
This study aims to systematically compare civics learning models of elementary schools in Indonesia and Finland. This study used the descriptive qualitative method with a literature review design. A systematic comparative literature review method was used, categorized as a configurative review. The data in this study consisted of secondary data sources, including scientific articles, books, and videos regarding civics learning models for elementary schools in Indonesia and Finland. The systems of civics learning models in Indonesia and Finland have several differences, such as: (1) the learning objectives of civics in Indonesia had a greater focus on cultivating character and multiculturalism; (2) the social system aspect is different; (3) the reflection and feedback aspects of civics learning are different; and (4) there are also differences in the instructional impact of civics learning. Meanwhile, the systems of civics learning models used in Indonesia and Finland have similarities, including: (1) civics learning in both countries aims to instill values related to rights, obligations, and democracy; and (2) both systems utilize contextual and experiential learning methods, including outdoor activities and real-life case discussions. Finland's civics learning model is considered more comprehensive and participatory, as it fosters critical thinking, civic engagement, and a deeper understanding of democratic values and societal functions. The novelty of this study lies in its use of a systematic comparative literature review to analyze the design, delivery, and impact of civics learning in two distinct educational contexts.